Mitigating academic boredom and increasing well-being among Chinese College students based on a positive education approach - Zheng, Jie; Roslan, Samsilah; Muhamad, Mohd.Mokhtar; Md Khambari, Mas Nida; Zaremohzzabieh, Zeinab (Richtmann Publishing, 2021)
Academic boredom is negatively related to students’ academic outcomes like intrinsic motivation. Positive education is dedicated to improving both students’ academic outcomes and wellbeing. In this study, China’s “6+2” positive education model was adopted to develop an intervention program that aimed to reduce academic boredom and improve positive emotions, thought-action repertoires, and intrinsic motivation. Theoretically, this emotion-oriented treatment is expected to cultivate positive emotions to broaden students’ attention scope, widen their thought and action repertoires, facilitate intrinsic motivation and build up enduring psychological resources that help them better cope with negative emotions like academic boredom and trigger upward spirals toward emotional wellbeing. This proposed model fills a research gap in existing interventions and provides new theoretical knowledge in terms of reducing academic boredom and improving academic success as well as wellbeing among Chinese college students. The theoretical framework of this study consisted of the broaden-and-build theory of positive emotions, basic psychological needs theory, and the control-value theory of academic emotions.